Analisis Pengaruh Pengalaman Dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan PT. Hari Mukti Teknik Yogyakarta Era Adaptasi Baru Pandemi Covid-19 - Agus Dwi Cahya; Anggoro Wisnu Aji; Dyko Utomo (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine the effect of work experience and Organizational Citizenship Behavior (OCB) on employee performance partially, and the effect of work experience and Organizational Citizenship Behavior (OCB) on employee performance simultaneously at PT. Yogyakarta Engineering Mukti Day. The research method used is quantitative with a population of 45 employees. Sampling using saturated non-probability sampling, with the entire population of 45 employees to be sampled. The data obtained were then processed using the Statistical Package for the Social Science (SPSS) version 22 for windows. The data collection technique used was a questionnaire using google forms for employees of PT. Yogyakarta Engineering Mukti Day. Data analysis techniques used in this study include reliability test, validity test, multiple linear regression test, classical assumption test through the T test, F test, and the coefficient of determination. The results of the study concluded that the variables work experience and Organizational Citizenship Behavior (OCB) partially affect the performance of employees at PT. Yogyakarta Engineering Mukti Day. The results of the study conclude that the variable work experience and Organizational Citizenship Behavior (OCB) simultaneously affect the performance of employees at PT. Yogyakarta Engineering Mukti Day.